KONSENTRASI LOGAM KADMIUM (Cd) DAN MERKURI (Hg) PADA KERANG HIJAU (Perna viridis) DI PERAIRAN CILINCING PESISIR DKI JAKARTA - Anna Rejeki Simbolon (Jurnal Pro-Life, 2018)
Abstract Green shell (Perna viridis) is one of the biota which is food and widely distributed in Cilincing waters. This research aims to know the heavy metal content of Kadmiun (Cd) and Mercury (Hg) in Cilincing Coastal Waters of DKI Jakarta. Green Hanger analyzed the metal content by AAS (Atom absorption spectrophotometer). The results of heavy metal content of Cd and Hg were analyzed descriptively based on the quality standard referring to the Decree of the Food and Drug Agency of the Republic of Indonesia (BPOM) of 2016 on the determination of the maximum limit of microbial and chemical contamination in food. The significance value of each sampling station in the test with one-way Anova test. The results showed that the metal content of Cadmium (Cd) ranged from 0.03 mg / kg-0.5 mg / kg. While the mercury metal content (Hg) in green shells (P. viridis) ranged from 0.02 mg / kg-0.06 mg / kg with anova assay results at each study site of p> 0.05. It shows the metal content of cadmium and mercury still in accordance with the standard quality that has been determined with the range of heavy metal content of both cadmium and mercury are not significantly different in each sample location. Keywords: Cadmium; Cilincing Waters; Heavy metal; Mercury